1999
DOI: 10.1002/(sici)1099-0755(199901/02)9:1<111::aid-aqc320>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Vertical movements by planktonic cyanobacteria and the translocation of phosphorus: implications for lake restoration

Abstract: 1. Vertical movements of cyanobacteria during summer stratification were studied in Cauldshiels Loch, a small dimictic temperate lake. 2. Filaments of the three species of cyanobacteria dominant in the summer phytoplankton were recorded moving vertically in both directions, by simple traps deployed just below the thermocline. 3. These phytoplankters could potentially exploit opposing ends of the vertical light/nutrient gradient that existed in the water column during stratification. 4. The hypolimnion and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The analysis of the variability of SRP and TP concentrations in the interstitial water of Uzarzewskie Lake showed that higher values were noted in summer and autumn periods at the station located in the profundal zone, as phosphorus released by the mineralization of organic matter in the sediments was enriching the interstitial water first; this was also found by Head et al (1999). A similar seasonal variability was recorded in the littoral zone.…”
Section: Discussionsupporting
confidence: 64%
“…The analysis of the variability of SRP and TP concentrations in the interstitial water of Uzarzewskie Lake showed that higher values were noted in summer and autumn periods at the station located in the profundal zone, as phosphorus released by the mineralization of organic matter in the sediments was enriching the interstitial water first; this was also found by Head et al (1999). A similar seasonal variability was recorded in the littoral zone.…”
Section: Discussionsupporting
confidence: 64%
“…Physical drivers, like upwelling and mixing events, may also promote blooms that are initiated when water temperatures are cold by providing hypolimnetic nutrients. Several taxa, such as Planktothrix , Dolichospermum , and even Microcystis , respond to lake mixing events that supply nutrients from the hypolimnion across the water column (Head et al 1999; Bormans et al 2016). These hypolimnion‐derived nutrients may then support late fall/early winter cyanobacterial blooms.…”
Section: Types Of Cold‐water Cyanobacterial Blooms: Modes Of Developmentmentioning
confidence: 99%
“…Migration velocities appear to be large enough to reach anoxic areas in many systems, but data are limited (Table ). Migration downwards into anoxic waters has been observed (Camacho et al ., ; Camacho, Vicente & Miracle, ; Gervais et al ., ) as well as acquisition of P during migration (Head, Jones & Bailey‐Watts, ). Aphanizomenon has been observed migrating upwards in the anoxic hypolimnion of Lake 227 in the Experimental Lakes Area in north‐western Ontario below the metalimnion (Fig.…”
Section: The Critical Role Of Ferrous Ironmentioning
confidence: 99%